Vision based solutions for autonomous navigation - Karunsekera, H. Hasith Ruchiran (Nanyang Technological University, 2021)
This thesis presents a study on computer vision solutions for autonomous navigation. Among many different functionalities in autonomous navigation, areas covered in this study include obstacle detection and multiple object tracking.